1996
DOI: 10.1046/j.1365-2125.1996.32311.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of co‐administration of benzhexol on the peripheral pharmacokinetics of oral levodopa in young volunteers

Abstract: 1 The effects of benzhexol on the absorption and pharmacokinetics of an oral dose of levodopa have been studied in 10 young healthy volunteers. Subjects were given a suspension of levodopa (250 mg) 90 min after either benzhexol (5 mg) or placebo in a randomized cross over design with doses separated by at least 1 week; on each occasion carbidopa was given 1 h before and 5 h after the dose of levodopa. Soluble paracetamol and radiolabelled DTPA were given with the levodopa as markers of gastric emptying. 2 Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
(7 reference statements)
1
4
0
1
Order By: Relevance
“…Some investigators have found a significant correlation between the parameters for the rate of paracetamol absorption and scintigraphically measured gastric half-emptying time, the "gold standard" for GER measurement, 9,[12][13][14][15] but others have failed to find such correlation. 16,17 Based on the absence of "significant" correlation, the validity of the paracetamol method has been challenged.…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Some investigators have found a significant correlation between the parameters for the rate of paracetamol absorption and scintigraphically measured gastric half-emptying time, the "gold standard" for GER measurement, 9,[12][13][14][15] but others have failed to find such correlation. 16,17 Based on the absence of "significant" correlation, the validity of the paracetamol method has been challenged.…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 95%
“…18 On the other hand, in research favoring the paracetamol method, the range of half-emptying time was expanded by enrolling patients with a possible disorder in GER 13 or by pharmacological interventions. 15 As a result, a significant correlation would be disclosed. Based on these findings, we believe that real correlation exists between the rate of paracetamol absorption and the scintigraphy-based measurement of GER, although the strength of the cor-…”
Section: Validity Of Paracetamol Methodsmentioning
confidence: 95%
“…Serial studies have documented definite relationships between scintigraphically assessed gastric emptying profiles and double‐peak patterns in the time versus plasma concentration curves of oral paracetamol, which is the gastric emptying marker, as follows: 7–10 (i) separation of a gastric emptying process by a period of very slow or quiescent emptying (the plateau) generates the double‐peak; (ii) the magnitude of the fraction emptied by the time at the beginning of the plateau is related directly to the relative size of the two peaks, with the larger the initial fraction emptied, the higher the initial peak concentration; (iii) the plateau phase emerges immediately after the initial peak is achieved; and (iv) the time at the end of the plateau period agrees with the time at the trough concentration. These scenarios have been reproduced very precisely by the Wagner‐Nelson method applied to OBT as shown above.…”
Section: Discussionmentioning
confidence: 99%
“…The [ 13 CO 2 ] excretion curve occasionally exhibits an atypical double‐peaking behaviour, which results in poor curve fitting 6 . Previous investigations on gastric emptying and paracetamol have suggested that plasma paracetamol concentration–time profiles manifest the double‐peak phenomenon when two emptying phases are separated by an interval of a quiescent (plateau) emptying phase 7–10 . Thus, it is reasonable to consider that the presence of the plateau emptying phase is also responsible for the occurrence of dual peaking [ 13 CO 2 ] excretion.…”
Section: Introductionmentioning
confidence: 99%
“…• Για την επίδραση διαφόρων φαρµάκων (φάρµακα χρησιµοποιούµενα κατά της ηµικρανίας 211,212 , χηµειοθεραπευτικά 213,214 , θεοφυλλίνη 215 , λεβοντόπα 216,217 , µη στεροειδή αντιφλεγµονώδη 218 , β-αγωνιστές 219 , σκευάσµατα ασβεστίου 220 και ιχνοστοιχεία 221 , ατροπίνη 222 , ασπιρίνη 223 , ντοπαµίνη 224 , αναστολείς διαύλων ασβεστίου 225 και διουρητικά 226 ) στην ΓΚ και την µελέτη της φαρµακοκινητικής τους.…”
Section: εφαρµογέςunclassified